Comparing the Quality of West Sumatra’s Rendang: Rendang Darek vs Rendang Pasisia - Yuliana Yuliana; Yolanda Intan Sari; Violintikha Harmawan (Diponegoro University, 2023)
The aim of this research is to compare the quality of beef rendang in the Darek and Pasisia regions using a standardized recipe. The recipe was a recipe obtained in the Darek region, called Payakumbuh City, and the Pasisia region, called Pariaman City. This research was quantitative research. Further, the informants of this study were Micro, Small, and Medium Enterprises or MSMEs in the Darek and Pasisia regions. Questionnaires and experiments were used to gain the data. Further, the data were analyzed using organoleptic analysis, which tested the shape qualities, color, aroma, texture, and taste. The scores were in the range of 1–5. Moreover, after determining the total scores resulting from each item score, the Man Whitney U test was conducted. The results showed that there were different qualities of beef rendang in the Darek and Pasisia regions in terms of shape, color, aroma, texture, and taste. As conclusion, there were different qualities of beef rendang in the Darek and Pasisia regions with specific value.